Make me a man! : masculinity, Hinduism, and nationalism in India - Banerjee, Sikata (SUNY series in religious studies., 2005)
"Make Me a Man! argues that ideas about manhood play a key role in building and sustaining the modern nation. It examines a particular expression of nation and manliness: masculine Hinduism. This ideal, which emerged from India's experience of British imperialism, is characterized by martial prowess, muscular strength, moral fortitude, and a readiness to go to battle." "Sikata Banerjee notes that the nationalism defined by masculine Hinduism draws on a more general narrative of nation found in many cultures. If the outcomes of this narrative are to be resisted, the logic of masculinity, armed manhood, and nation need to be examined in diverse contexts."--Jacket